PEMBELAJARAN TEMATIK TERPADU DENGAN PENDEKATAN SAINTIFIK DI SEKOLAH DASAR NEGERI KECAMATAN TERIAK - Indra Yuliwati; Mashudi Mashudi; Tahmid Sabri (Universitas Tanjungpura, 2021)
AbstractThe research focus states that integrated thematic learning with saintific approach within Publick Primary School 07 Dungkan Districk Teriak Bengkayang Region. The purpose of this research is to analyze the integrated thematic learning with saintific approach..The informans of this research are the head master, grade IV class teacher and students grade IV Publick Primary School 07 Dungkan. The research method used is descriptive qualitative. The collecting data technic used were observation, interview, and the documents. The data analyzed of this research was descriptive qualitative. The research data results showed, that the integrated thematic learning with saintific approach have been going on in accordance with 5 steps of saintific activities,namely observing, questioning, trying,reasoning, and communicating. She didn’t implement assessment of affective and motoric students competencies. The head master did help by giving chances to her to follow KKG, discuss with peer teching who haved a good experience to solv the problem.Keywords: Approach, Learning, Saintific, Thematic, The Integrated